Epidemiology of hepatitis A in Greece in the last decade: management of reported cases and outbreaks and lessons learned. (13th February 2020) - Mellou, K.; Chrysostomou, A.; Sideroglou, T.; Kyritsi, M.; Georgakopoulou, T.; Tsiodras, S.; Hadjichristodoulou, C.
Abstract: Hepatitis A is a mandatory notifiable disease in Greece. Here, we present the epidemiological data for 2009–2018 and the results of outbreak investigations performed, and discuss future public health priorities. Overall, 1193 cases were reported; 320 migrants/refugees, 240 Roma, 112 travellers and 521 from the general population. The median age of the affected general population (37 years) had an increasing trend (from 30.8 years in 2009 to 40.5 in 2018, P < 0.001) and was significantly higher than that among Roma and migrants (7 and 8 years, respectively, P < 0.001). Twenty-two cases (2.2%) were unvaccinated patients with a chronic liver disease. Fifty clusters with 2–12 cases each were recorded; 44 were attributed to person-to-person transmission and six to food consumption. Three outbreaks accounting for 32.3% of the total number of recorded cases were identified; in 2013 among Roma (112 cases), in 2016 among refugees (188 cases) and in 2017 among men having sex with men (96 cases; 33 of them (34.4%) HIV-positive). The epidemiological data depict that improving living conditions and vaccination coverage of deprived populations, and informing adults on the disease focusing at faecal–oral transmission during sexual intercourse and travel should be the future public health priorities.